PENJATUHAN SANKSI PIDANA MATI TERHADAP PELAKU TINDAK PIDANA PEMBUNUHAN BERENCANA DITINJAU DARI UNDANG-UNDANG NOMOR 39 TAHUN 1999 TENTANG HAK ASASI MANUSIA - Buulolo, Alinus (Jurnal Panah Hukum, 2025)
The issue with this research is that it violates human rights to execute criminals, so the death penalty is inappropriate as a form of punishment. The purpose of this study is to ascertain whether the death sentence should be applied to those who commit premeditated murder in accordance with Human Rights Law Number 39 of 1999. Normative legal research is the kind of study that this is. The findings of the study demonstrate that everyone has an inalienable right to life and existence. The rights of others also place restrictions on these rights. Because essentially crimes against humanity and genocide are considered severe crimes that are punishable by death in Human Rights Courts under Article 7 of Law Number 26 of 2000 concerning Human Rights Courts. The defendant, Musliadi Kataren Als Musli Bin Banta Kataren, was given the death punishment because of his conduct, which included premeditated murder of three victims. The researcher makes the following recommendations: 1) If Indonesia continues to desire to include the death penalty in its positive legislation, it is hoped that a special rule will be created that unequivocally validates the application of the death penalty for a number of exceptional offenses in Indonesia. Hopefully, in the future, this won't lead to debates between specialists, human rights advocates, and 2) It is envisaged that the death penalty in Indonesia will no longer be a fundamental crime but rather an alternate punishment used for exceptional offenses with the writing of the new Criminal Code.